Firm Value as an Intervening Variable in the Relationships of Liquidity, Leverage, and Profitability in the Hospitality and Tourism Sector - Kepramareni, Putu; Pradnyawati, Sagung Oka (AIBPM Publisher, 2024)
One of the benchmarks in assessing the success of an investment activity is based on the acquisition of stock returns. During the pandemic, the hotel, restaurant and tourism industry sector was very significantly affected, various travel restriction policies to the closure of tours caused a drop in capital market activity in this sector. The author uses firm value as a mediation to examine various factors such as profitability, liquidity and leverage which can affect stock returns in the hotel, restaurant and tourism industry sector. Financial report publications are used as data sources and research objects which are then analyzed and studied using Partial Least Square (PLS) as a test tool.Testing and analysis obtained the fact that the ratio of the ability to fulfill current liabilities (liquidity), the ratio of debt (leverage) and the ratio of profits (profitability), significantly affect the formation of firm value and firm value can directly affect stock returns but as a whole the variables cannot provide significant direct effect on stock returns without being mediated by firm value.